Cultural studies in Central America - Fumero Vargas, Patricia (2013)
This article studies the epistemological change towards cultural studies in Central America. It discusses diverse approaches that influenced towards this change. I analyze the problematic that cultural studies opens in terms of its diversity and development of comparative studies. Finally, I asses the accomplishments made by literary studies, specifically those related with transdisciplinary and interdisciplinary research program "Hacia una historia de las literaturas centroamericanas" (HILCAS) and the milestones that the regional research must confront.